2023
DOI: 10.1017/s1368980023002100
|View full text |Cite
|
Sign up to set email alerts
|

Effects of front-of-package caffeine and sweetener disclaimers in Mexico: cross-sectional results from the 2020 International Food Policy Study

Laura Patricia Arellano-Gómez,
Alejandra Jáuregui,
Claudia Nieto
et al.

Abstract: Objective: Front-of-pack warning labels introduced in Mexico in 2020 included disclaimers that caution against allowing children to consume products with non-sugary sweeteners and caffeine. We examined the awareness and use of the disclaimers among Mexican adults and youth one month after the regulation was implemented. We also investigated their impact on the perceived healthfulness of industrialized beverages designed for children. Design: Data on the awareness and use of the disclaime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…In our study, participants with lower educational level, lower income adequacy and indigeneity status self-reported a greater reduction in the purchase of unhealthy foods because of the WLs. These population groups have a disproportionate burden of noncommunicable diseases and lower access to healthy and nutritious foods [39]. Results of this study suggest that WLs may aid in decreasing health disparities.…”
Section: Discussionmentioning
confidence: 78%
“…In our study, participants with lower educational level, lower income adequacy and indigeneity status self-reported a greater reduction in the purchase of unhealthy foods because of the WLs. These population groups have a disproportionate burden of noncommunicable diseases and lower access to healthy and nutritious foods [39]. Results of this study suggest that WLs may aid in decreasing health disparities.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, in addition to the traditional WLs indicating excess content of critical nutrients, many sugary drinks in Mexico are also required to display the two rectangle-shaped warning legends related to sweeteners and caffeine content [38]. These additional labels, which are generally less applicable to other food categories, may contribute to changes in the perceived healthiness of cola beverages and artificially sweetened drinks [38,39]. For example, the perceived impact of WLs on sugary fruit drink purchases was significantly lower than on diet soda purchases among youth (although no difference was observed among adults) [39].…”
Section: Discussionmentioning
confidence: 99%
“…These additional labels, which are generally less applicable to other food categories, may contribute to changes in the perceived healthiness of cola beverages and artificially sweetened drinks [38,39]. For example, the perceived impact of WLs on sugary fruit drink purchases was significantly lower than on diet soda purchases among youth (although no difference was observed among adults) [39]. In line with the former, data from ENSANUT 2021 suggested that one year after the enactment of WLs in Mexico, 21.6% of adults identified excess calories in cola beverages, 82.3% identified excess sugars, 22.4% identified the caffeine warning, and 11.8% identified the sweeteners warning [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation